New Insights into Crop Molecular Breeding and Genetics - Yaqi Su; Zhen Cheng; Jiezheng Ying; Chaolei Liu; Zhiyong Li (Agronomy)
As the global population continues to grow, the need to increase agricultural productivity is becoming increasingly urgent [...]